Progestins and combined oral contraceptives in the hormonal treatment of endometriosis – a review - Rojek, Kornelia; Juda, Agata; Kamińska, Magdalena; Strzoda, Adam; Strzoda, Anna; Sowiński, Wojciech; Zdybel, Michał; Strzoda, Agata (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Endometriosis is a common inflammatory disease affecting 6-10% of women of reproductive age. It is defined as the growth of endometrial-like tissue outside the uterine cavity. Dysmenorrhea, pelvic pain, dyspareunia and infertility are the main symptoms of endometriosis patients. Endometriosis treatment methods can be broadly divided into surgical and pharmacological. Currently, hormonal drugs are often used for women with endometriosis to relieve bothersome symptoms. The aim of this article is to review new publications presenting the effectiveness as well as side effects of the use of progestins and combined oral contraceptives in the hormonal treatment of endometriosis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A review of the literature regarding progestins and combined oral contraceptives in the treatment of endometriosis was performed using the PubMed database. In the end, 67 articles were included in this review. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Progestins and combined oral contraceptives significantly reduce dysmenorrhea, dyspareunia and pelvic pain in women with endometriosis. However, there is a risk of potential side effects, which should be taken into account when choosing a therapy for each patient individually. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Endometriosis is a chronic disease that has a significant impact on the health-related quality of life of patients. When choosing a treatment, many aspects should be considered, primarily the patient’s preferences, drug tolerance and safety. Further drug research is needed to determine the most effective treatment for endometriosis.